Prevalence of suicidal behavior and its associated factors among individuals living in war-affected areas of Dessie Town, northeast Ethiopia, in 2022: a cross-sectional study - Birhan, Zelalem; Shegaw, Maregu; Kunno, Kunuya; Anbesaw, Tamrat; Woretaw, Lebasie; Tedla, Assasahegn; Munie, Birhanu Mengist; Belete, Asmare (Frontiers in Psychiatry, 2025)
BackgroundGlobally, suicide is a serious public health issue, especially in areas devastated by conflict where trauma and psychological anguish are prevalent. War has long-lasting impacts on mental health, particularly increasing the risk of suicidal behavior among survivors. Suicidal ideas and attempts must be promptly identified and handled, even though suicide cannot be directly treated. The prevalence of suicidal behavior in war-affected areas remains poorly understood. Existing studies often focus on high-income countries, leaving a gap in knowledge for low- and middle-income countries like Ethiopia, specifically in Dessie Town. This study aimed to assess the prevalence of suicidal behavior and its associated factors among individuals living in a war-affected area, Dessie Town, Northeast Ethiopia.MethodsA community-based cross-sectional study was conducted among adult residents in the war-affected area, Dessie Town. A total of 617 individuals were selected by a systematic random sampling method. Suicidal behavior was assessed using the Mini International Neuropsychiatric Interview suicidal behavior screening tool. Multivariable logistic regressions were used to measure the associated factors. Associations of variables were described by using odds ratios (ORs), 95% confidence intervals (CIs), and p-values less than 0.05.ResultsThe prevalence of suicidal behavior in these participants was 15.3% (95% CI: 12.5, 18.3). Factors significantly associated with suicidal behavior included being divorced or widowed (AOR: 2.19, CI: 1.06, 4.50), being unemployed (AOR: 2.11, CI: 1.16, 3.83), having depression (AOR: 3.11, CI: 1.80, 5.39), having post-traumatic stress disorder (PTSD) (AOR: 1.96, CI: 1.12, 3.43), stressful life events (AOR: 3.80, CI: 1.97, 7.36), and having poor social support (AOR: 3.40, CI: 1.71, 6.78).Conclusion and RecommendationThe findings highlight a significant burden of suicidal behavior among survivors of conflict-affected areas in northeast Ethiopia, an under-researched population, emphasizing the need for integrated mental health and psychosocial support services tailored to war-affected communities. The following are the determinants of suicide behavior: being divorced or widowed, unemployed, depressed, suffering from PTSD, experiencing stressful life events, and having inadequate social support. These groups should be prioritized for interventions in resource-limited settings. To improve and lessen the signs of suicidal behavior and to optimize the quality of life for those who survive post-war, intervention is necessary.